Association Analysis of WNT3, HLA-DRB5 and IL1R2 Polymorphisms in Chinese Patients With Parkinson’s Disease and Multiple System Atrophy - Su, Wei-Ming; Gu, Xiao-Jing; Hou, Yan-Bing; Zhang, Ling-Yu; Cao, Bei; Ou, Ru-Wei; Wu, Ying; Chen, Xue-Ping; Song, Wei; Zhao, Bi; Shang, Hui-Fang; Chen, Yong-Ping (Frontiers in Genetics, 2021)
Background: The association between inflammation and neurodegeneration has long been observed in Parkinson’s disease (PD) and multiple system atrophy (MSA). Previous genome-wide association studies (GWAS) and the meta-analysis have identified several risk loci included in inflammation-relative genes associated with PD. Objective: To investigate whether polymorphisms in some inflammation-relative genes could modulate the risk of developing PD and MSA in a Southwest Chinese population. Methods: A total of 2706 Chinese subjects comprising 1340 PD, 483 MSA and 883 healthy controls were recruited in the study. Three polymorphisms in genes linked to inflammation in all the subjects were genotyped by using the Sequenom iPLEX Assay. Results: The allele G of WNT3 rs2074404 can increase risk on PD (OR:1.048, 95%CI:1.182-1.333, P=0.006), exclusively in the LOPD subgroup (OR:1.166, 95%CI:1.025-1.327, P=0.019), but not in EOPD or MSA. And the recessive model analysis also demonstrated an increased PD risk in GG genotype of this locus (OR=1.331, p=0.007). However, no significant differences were observed in the genotype and alleles distributions of HLA-DRB5 rs17425622 and IL1R2 rs34043159 between the PD patients and controls, between the MSA patients and controls, or between subgroups of PD or MSA and controls. Conclusion: Our results suggested the allele G of WNT3 rs2074404 has an adverse effect on PD, particularly on the LOPD subgroup among a Chinese population.